2019
DOI: 10.3168/jds.2018-15396
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Production of antimicrobial peptide S100A8 in the goat mammary gland and effect of intramammary infusion of lipopolysaccharide on S100A8 concentration in milk

Abstract: This study aimed to determine the production site of antimicrobial peptide S100A8 in the goat mammary gland and changes in its concentration in milk after lipopolysaccharide (LPS) challenge. Sixteen Tokara goats were used in this study for mammary gland tissue, blood leukocyte, and milk somatic cell collection and LPS challenge. The mRNA expression and protein localization of S100A8 in the mammary gland parenchyma and teat, blood leukocytes, and milk somatic cells were examined by reverse-transcription PCR and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 42 publications
3
15
0
Order By: Relevance
“…On the other hand, goat mastitis model was established in vitro using goat MECs treated by LPS. LPS, which is a cell wall component of Gramnegative bacteria, were widely used to induce mastitis model in vivo and in vitro [52,53,54,55]. Consistent with previous reports, after treatment with LPS, the in ammatory response related factors including IL-6, IL-1β and TNF-α were obviously increased.…”
Section: Discussionsupporting
confidence: 77%
“…On the other hand, goat mastitis model was established in vitro using goat MECs treated by LPS. LPS, which is a cell wall component of Gramnegative bacteria, were widely used to induce mastitis model in vivo and in vitro [52,53,54,55]. Consistent with previous reports, after treatment with LPS, the in ammatory response related factors including IL-6, IL-1β and TNF-α were obviously increased.…”
Section: Discussionsupporting
confidence: 77%
“…This rapid response played an important role in the clearance of early intramammary infection. On the other hand, these results also help to explain the previous reports in which after LPS intramammary infusion, the increased concentration of S100A7 was 48 h earlier than S100A8 [21,25]. When bacteria invasion or LPS infusion in mammary alveolus, they rstly stimulated mammary epithelial cells to secrete S100A7, then leukocytes in ltrated mammary alveolus and secreted S100A8 into milk.…”
Section: Discussionsupporting
confidence: 76%
“…The teat skin is consistently exposed to external environment, and streak canal may remain open for short time after milking [23]. Considering that E. coli is one of the most important environmental pathogens [24], the constitutive expression of S100A7 and other AMP, for example S100A8 [25] in teat suggested their critical roles in innate immunity in teat which as a rst barrier to limit pathogens invasion.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, goat mastitis model was established in vitro using goat MECs treated by LPS. LPS, which is a cell wall component of Gram-negative bacteria, was widely used to induce mastitis model in vivo and in vitro ( 42 45 ). It is reported that LPS from the commensal microbiota of the human breast induced the expression of S100A7 in breast cancer cells ( 46 ).…”
Section: Discussionmentioning
confidence: 99%